Intangible capital, markups and profits - Maria Sandström (Uppsala University, Department of Economics, 2020)
Can an increasing importance of intangible capital explain increases in markups and profits? I use a heterogeneous firm model to show how intangible capital, characterized by fixed costs and uncertainty, is related to markups and profits at the industry level. The scalability and uncertainty properties of intangible capital imply that firms which succeed in their intangible capital investment can charge high markups relative to other firms whereas firms that fail will exit. However, these high markups do not imply any economic profits in the industry if they only serve to cover the total fixed costs of intangible capital. To empirically examine the relationship between intangible capital, markups and profits, I study average markups and profit shares in a panel of Swedish industries. There is evidence of a positive relationship between intangible capital and average industry markups. However, the evidence of the relationship between intangible capital and profits is less conclusive.
urn:nbn:se:uu:diva-417027
Keywords: E2; D2; L1; L2; 330; Intangible capital; Markups; Profits; Labor share; Market Power